Construing emotion in academic writing: L2 writers' use of Affect in historical explanation essays. (30th May 2018) - Myskow, Gordon; Ono, Masumi
Abstract : Writing about historical change involves advancing causal explanations that show how events impact people and how their emotions contribute to historical outcomes such as wars and revolutions. This study uses Martin and White's (2005) Appraisal framework to examine how the language of emotion (Affect), an overlooked feature of historical discourse, is used by L2 writers of an under-examined genre, the Factorial Explanation. The study was conducted in a content-based, politicalhistory course for 63 upper-intermediate learners of English at a Japanese university. Results show that while writers made extensive use of the Affect categories Positive Inclination and Negative Satisfaction, which were often realized as adjectives and verbs, nominal formulations for building cohesion were infrequent. Writers also tended to intensify Affect resources by construing feelings as static attributes rather than destabilizing forces of change. The paper makes recommendations for teaching genre-specific language features to aid learners in construing the emotion of history.